ANALISIS YURIDIS KEKUATAN HUKUM YURISPRUDENSI SEBAGAI DASAR PERTIMBANGAN HAKIM DALAM MEMUTUS TINDAK PIDANA PERZINAHAN (Studi di Pengadilan Negri Kelas I A Tanjung Karang) - Lukmanul Hakim; Ryan Ramadhan (KEADILAN PROGRESIF, 2021)
The role of jurisprudence in Indonesia is so important, apart from being a source of jurisprudential law, it becomes a guide for judges in deciding cases.Jurisprudence is a court decision that has permanent legal force. There are weaknessesin the formulation of Article 284 of the Criminal Code, so judges can make a kind oflegal discovery by exploring the values prevailing in society in order to decide courtcases. The problems in this study are as follows: 1) How is the legal force ofjurisprudence as the basis for judges' considerations in the settlement of cases ofadultery; 2) How is the determination of jurisprudence as a binding source of law inreflecting a sense of justice, providing benefits and guaranteeing legal certainty. Thisresearch method uses a normative juridical approach obtained from literature writing(Library Research) and Field Research (Field Research) using secondary and primarydata, and data analysis with qualitative juridical analysis. The results of the study showthat it is the judge who is most responsible for incorporating or combining juridical andnon-juridical elements through the decisions he makes. However, the threateningdecision handed down by the judge also does not provide a deterrent effect to theperpetrators and cannot be used as a lesson for other parties who have the potential tocommit the crime. A judge's decision must not only be fair, but must be beneficial for the person concerned and the community and guarantee legal certainty. The suggestion submitted is that it is hoped that judges who handle adultery crimes in the future takeinto account social, cultural and moral values that apply in the midst of people's lives,and not only base their decisions on juridical provisions alone.